A study of the influence of the COVID-19 pandemic on tourist behaviour and expectations: A case of Serbia - Mandarić, Marija; Sekulić, Dejan; Davidson, Rob (Hotel and Tourism Management, 2022)
Due to the spread of COVID-19 and the closing of the borders of a large number of countries, tourists’ interest in domestic tourist destinations has grown. The objective of this paper is to identify future behaviour patterns of tourists and to propose measures that would affect the interest of domestic tourists in domestic destinations after COVID-19. The study starts with an analysis of the impact of COVID-19 on global tourism, then focuses on trends in the tourism market in Serbia and ends by examining citizens’ attitudes towards key factors for domestic tourism development. It is estimated that tourism can benefit from an essential understanding of tourists’ demands for a safe journey. Research results indicate statistically significant differences in the attitudes of respondents in relation to age, gender and education, but most respondents believe that it is necessary for the state to invest more in tourist infrastructure and to adjust pricing policy to remain competitive domestic destinations after Covid-19.